SYNTAX, STS and EuroSCORE – How good are they for risk estimation in atherosclerotic heart disease? - Metzler, Bernhard; Winkler, Bernhard (Thrombosis and Haemostasis, 2012)
Tests that enable prediction of adverse outcome after surgical or nonsurgical intervention in cardiac patients are of great importance since they can help guide clinical decision making. The new evolving percutaneous therapeutic techniques combined with the currently available risk scoring systems require improved prediction models. In the context of steadily improving surgical techniques and perioperative care, on the one hand, and the inadequacy of regional patient data sets to provide generally applicable risk prediction base, on the other, there is need for adaption and recalibration of scoring systems some of which are partly outdated but still widely in use. The accuracy of predictive models depends on their proper application as well as the knowledge of their individual strengths and weaknesses. The EuroSCORE and the STS score take into consideration some risk factors associated with mortality, whereas the SYNTAX score relies solely on coronary anatomy and lesion characteristics. A combination of selected score components from the EuroSCORE, assessing the mortality risk, and those from the SYNTAX score, reflecting the coronary artery disease complexity, can be expected to yield more accurate results in estimating risk in individual patients. In this review, the predictive ability of the SYNTAX score, the STS score and the EuroSCORE will be discussed.
Keywords: Surgery; cardiology; risk factors